High rates ofMycobacterium fortuitumisolation in respiratory samples from Iranian patients with suspected tuberculosis: is it clinically important?. Issue 9 (September 2018) - Irandoost, Mahsa; Ghanbari, Mehrnoosh Zare; Sakhaee, Fatemeh; Vaziri, Farzam; Jamnani, Fatemeh Rahimi; Siadat, Seyed Davar; Fateh, Abolfazl
Abstract : Purpose. : Although Mycobacterium fortuitum ( M. fortuitum ) is not an organism rarely isolated from respiratory samples, its clinical importance is still not fully understood, which therefore prompted our current study. Methodology. : We evaluated respiratory samples from 6800 patients with suspected tuberculosis from May 2014 to May 2016, for the detection of M. fortuitum using phenotypic and genotyping methods. Results/Key findings. : Of the 40 patients with M. fortuitum lung disease, 35 had two or more positive culture results. The mean age of these 35 patients was 50.7±18.4 years, and 20 (57.1 %) were men. Sputum (68.6 %), haemoptysis (51.4 %), cough (45.7 %) and gastroesophageal disease (22.9 %) were the major presenting symptoms. Cystic fibrosis, other bacterial lung diseases and lung cancer were the main underlying pulmonary diseases. Five patients (12.5 %) were human immunodeficiency virus (HIV) positive. The most common chest X‐ray findings were reticulonodular opacities (53.3 %). Multivariate logistic regression analysis revealed that cigarette smoking history (OR 0.334, 95 % CI 0.125–0.843, P =0.048) and underlying lung disease (OR 0.393, 95 % CI 0.216–0.588, P =0.023) were significant predictors for positive M. fortuitum infection. Conclusion. : These results demonstrated the high frequency of M. fortuitum in respiratory samples and that this bacterium causes transient infection or colonization in patients with underlying pulmonary conditions, such as cystic fibrosis and cigarette smoking‐induced. Additionally, it appears that infection with M. fortuitum is particularly common and may be important in patients with HIV.